Effectiveness of Combined Physical – Cognitive Training on Balance among Geriatric Population - Fhebe, Moses; Kumaresan, Abathsagayam; Surya, Vishnuram; Prathap, Suganthirababu; Vignesh, Srinivasan; Ramana, Kameswaran; Vinodhkumar, Ramalingam; Pavithra, Aravind (INTI International University, 2023)
Introduction: Each year, almost one-third of the elderly fall, and the likelihood of falling increases with age. Combining physical and cognitive training may be an effective intervention for fall risk reduction and cognitive enhancement. Physical and cognitive interventions, such as exercise and cognitive training, may be used to address the decline in cognitive function as well as the presence of some physical fall-related risk factors, such as decreased balance control, muscle weakness, and a slow gait, which predispose older adults to fall. Physical and cognitive abilities training can help to prevent or slow the onset of age- related cognitive decline. Aim: To Determine the Effectiveness of Combined Physical- Cognitive training on Balance among Geriatric population. Objective: To find out the effectiveness of combined physical – cognitive training on balance and cognitive function among geriatric population using Berg Balance Scale and Mini Mental State Examination. Methodology: This study is a quasi-experimental study. The study was conducted with sample size of 15 participants. The participants were selected from SCPT out-patient and SMCH hospital, according to the inclusion and exclusion criteria. The detailed procedure was explained to the participants and a written informed consent form was obtained. All the 15 subjects were assessed with Berg Balance Scale and Mini Mental State Examination as a pretest and the same test was performed for post-test at the end of 4 weeks following the intervention protocol. All the 15 subjects received the combined training of physical and cognitive training for 60 mins, 3 sessions in a week, continued for 4 weeks. Results and Conclusion: Combined physical cognitive training is more effective on improving balance and cognitive function in geriatric population than using of a single treatment protocol.